2011
DOI: 10.1002/etc.647
|View full text |Cite
|
Sign up to set email alerts
|

Strong associations of short‐chain perfluoroalkyl acids with serum albumin and investigation of binding mechanisms

Abstract: Interactions of perfluoroalkyl acids (PFAAs) with tissue and serum proteins likely contribute to their tissue distribution and bioaccumulation patterns. Protein-water distribution coefficients (K(PW) ) based on ligand associations with bovine serum albumin (BSA) as a model protein were recently proposed as biologically relevant parameters to describe the environmental behavior of PFAAs, yet empirical data on such protein binding behavior are limited. In the present study, associations of perfluoroalkyl carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
122
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 46 publications
(89 reference statements)
10
122
2
Order By: Relevance
“…[37][38][39] Keratin protein is the main component of hair. The occurrences of PFOA, PFNA, and PFOS in hair, and the similar profile to that in the main tissues, suggested that the affinity of PFAAs to keratin possibly play a dominant role in the hair PFAA accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Keratin protein is the main component of hair. The occurrences of PFOA, PFNA, and PFOS in hair, and the similar profile to that in the main tissues, suggested that the affinity of PFAAs to keratin possibly play a dominant role in the hair PFAA accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in renal clearance of PFCAs with differing chain lengths have primarily been attributed to their binding affinities to serum albumin and different sets of organic anion transporter proteins that govern the reabsorption of PFCAs from urine to blood. 55−57 A recent study that investigated bovine serum albumin-water distribution coefficients (K PW ) demonstrated a positive association between binding affinities and the perfluoroalkyl chain, 56 and the few data so far on human elimination of short-chain PFCAs indicate a substantially faster clearance of PFBA compared to PFHxA. 17,18 Interestingly, our data displayed similar or slightly lower clearance rates for PFBA compared to PFHxA and PFHpA (Figure 3), although no significant differences were observed for clearance rates among these three PFCAs according to the statistical test.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The distribution of PFASs in proteinrich tissues, rather than in fat tissues, and the high affinity to some proteins highlighted the proteinophilic nature of PFASs Bischel et al, 2011Bischel et al, , 2010. Though the serum proteins do not exist in plants, fatty acid binding proteins have been found in plants (Arondel et al, 1990;Rickers et al, 1984).…”
Section: Relationships Between the Contents Of Protein And Lipid And mentioning
confidence: 99%